Percepção dos impactos dos cursos de MBA oferecidos no Brasil na carreira profissional dos seus estudantes - Migliora Neto, Luiz Ernesto José (2020)
The MBA programs studied are standardized, which allow a high scale comparison in a nationwide research performed through quantitative methodology of data survey, with cross section, by means of managed questionnaires. There were three questionnairesrespectively sent to: 16.144 students, with minimum one year of MBA class room experience, with 1.527 answers (9,46%); 75.660 of already graduated students from MBA classes within the last five years, with 6.658 answers (8,80%); and 1.344 employers of enterprises, with 115 answers (7,88%). It was identified student’s age in average is of 35 years and 11 of years professional experience, with medians of 40 and 5 years respectively. More than 40% have been in post-graduation programs before joining the MBA, and approximately 58% of the student are from large organizations, majority of middle management. Respondents of questionnaires state that: approximately 80 to 88% that the MBA attended their expectations, and those statistics were confirmed by the result of multiple regressions herein in the study. There were different kinds of subjective impacts identified by the respondents: increase of confidence and of technical capacity by 80 to 88%, readiness to assume leadership positions and people management functions by 70 to 75%, increase of prestige amongst their peers and superiors by 65 a 70%, the student feels more motivated and satisfied with their career by 65 a 70%, increase of employability within the enterprise by 50 to 65%, achieved a professional objective by 50%, and 65% considers to have improved the level of customer service. In the multiple regressions with the dependent variable (Y) the MBA attended student’s expectation, the independent variables explained 57% of the variability (Y) for students in MBA class, 52% of the variability (Y) for graduated students and 63% of variability of female gender students in MBA classes. In the multiple regression considering the dependent variable (Y) the MBA attended the organization’s expectation, the independent variables explained 62% of the variability (Y). However, just approximately 50% of graduated dos student, 35% of employers and 22% of students in MBA class received increase on compensation and according to the multiple regressions, these increases were not related to the MBA. As recommendation, the introduction of EMBA, verification of new subjects, professors with proven executive experience, seminaries and debates via webinars with topics of great interest to them, in the spirit of continuous executive education.